WORD FORMATION ON DRAGON NEST CHAT LANGUAGE - Harsono, Shavitri Cecillia (Jurnal Bahasa Lingua Scientia, 2016)
Word formation is creation of new words, which sometimes changes a wordâs meaning. Words can be formed from multi word phrases as well. In many cases vocabularies in language are formed from combination of words (Haspelmath 2010: 102). Word formation does not only involve changing physical form of the word itself, but also changing the meaning of said word. There are also instances where the physical form retain its original form while the meaning changes. The phenomenon is called semantic change (Stockwell-Minkova 2001:149). In this thesis the research proposed that the said phenomenon occur in virtual environment, such as in MMORPG. Multiplayer online games that feature fantasy setting virtual environment. For the purpose of this research, Dragon Nest South East Asia server was chosen as data source. The samples are taken from players perusing [World] communication channel. The result of the data analysis has shown that the phenomenon of word formation could occur in a virtual environment of MMORPG, specifcally in Dragon Nest SEA. There are two word formation processes found: processes that involve physical changes and processes that do not involve physical changes but rather innate meaning. It is done by both processing daily language vocabulary both physically and changing its innate meaning to create new words that suits the said virtual environment context. This fnding may inï¬uence future research on a fresh perspective and untilled feld.